Art and social justice the media connection - Hajimichael, Michael (Cambridge Scholars Publishing, 2015)
"This book is a collection of articles that reflect on various connectivities between art and social justice and media which are pertinent to studying contemporary societies. How different forms of media and art, in the broadest possible meaning of these terms, reflect on, relate to, and campaign for social justice is an important topic to consider as artists, academics and activists." -- Provided by publisher